PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE SYNERGETIC TEACHING TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 2 KOTO XI TARUSAN KABUPATEN PESISIR SELATAN - Gusmaningsih, Lukita; Husna, Husna; Cesaria, Anna (STKIP PGRI Sumbar, 2014)
Â ABSTRACTStudents understanding of mathematical concept are still low in class VIII SMPN 2 Koto XI Tarusan become the background for this study. This research was designed for revealing whether the use of Synergetic Teaching active learning strategy could improve the students understanding of mathematical concept better than that of the conventional learning in class VIII SMPN 2 Koto XI Tarusan. This was an experimental research which used random toward the subject design. The instrument of the research was a post-test of conceptual understanding. The data of the research was analyzed by using Mann-Whitney test. Based on the result of data analysis, it was found that Â which was smaller than Î±. Therefore, the hypothesis was accepted signifying that the students understanding of mathematical concept taught by using Synergetic Teaching active learning strategy was better than that of students taught by using conventional learning in class VIII SMPN 2 Koto XI Tarusan.